PERANCANGAN APLIKASI PENGOLAHAN DATA KELOMPOK TANI TERNAK PROVINSI NTB - Azwar, Muhamad; Moch. Syahrir; Mudawil Qulub (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
The Department of Animal Husbandry and Animal Health is one of the government agencies of West Nusa Tenggara Province which has the task of improving the welfare of the community and reducing poverty in West Nusa Tenggara Province by providing grants in the form of livestock assistance or other assistance, assistance is given to livestock farmer groups in all regencies/cities throughout the province. -NTB has criteria that have been determined by the Animal Husbandry and Animal Health Service of the Province of NTB, the assistance provided is sourced from the Provincial Revenue and Expenditure Budget (APBD) and the State Revenue and Expenditure Budget (APBN), because the process of providing assistance through the selection of submitted proposals manually by livestock farmer groups with three processes that become important points, namely recapitulation, validation and verification which takes a long time and the lack of information related to the development of livestock farmer groups in all regions of NTB that have received assistance, therefore an application or application is needed. u an information system that can assist the Department of Animal Husbandry and Animal Health of the Province of NTB in processing livestock farmer group data, ranking as a good decision maker..